1994
DOI: 10.1128/mcb.14.9.6208
|View full text |Cite
|
Sign up to set email alerts
|

Two distinct factors bind to the rabbit uteroglobin TATA-box region and are required for efficient transcription.

Abstract: The rabbit uteroglobin gene is expressed in a variety of epithelial cell types like the lung Clara cells and the glandular and luminal epithelial cells of the endometrium. Expression in Clara cells is on a high constitutive level, whereas expression in the rabbit endometrium is under tight hormonal control. One important element of the rabbit uteroglobin gene mediating its efficient transcription in two epithelial cell lines from human endometrium (Ishikawa) and lung (NCI-H441) is its noncanonical TATA box (TA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 59 publications
1
23
0
Order By: Relevance
“…1B). But previous results had shown that the wild-type promoter with its TACA box is sevenfold less active in driving reporter gene expression in CV-1 cells than a single-point mutant converting the TACA box to a TATA box (27). A very similar result was obtained with the TACA box of the adenovirus type 2 (Ad2) EIIa late promoter (EIIaL) (21).…”
supporting
confidence: 63%
See 4 more Smart Citations
“…1B). But previous results had shown that the wild-type promoter with its TACA box is sevenfold less active in driving reporter gene expression in CV-1 cells than a single-point mutant converting the TACA box to a TATA box (27). A very similar result was obtained with the TACA box of the adenovirus type 2 (Ad2) EIIa late promoter (EIIaL) (21).…”
supporting
confidence: 63%
“…Likewise, the ability of this TACA box to mediate activation by modulatory transcription factors was reduced by a factor of 10. Similarly, it was shown that a uteroglobin mutant in which the wild-type TACA box was converted to a TATA box is sevenfold more active than the wild-type construct in driving reporter gene expression in CV-1 cells (27). But in contrast to the rabbit gene, the human (score of Ϫ1.36) and the mouse and rat (score of Ϫ1.50) uteroglobin genes have bona fide TATA boxes with matrix scores not much lower than that of one of the strongest TATA boxes known, the Ad2 major late promoter TATA box (score of Ϫ0.91).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations